Calidad fisicoquímica del producto terminado Dorzolamida 2 % + Timolol 0,5 % solución oftálmica de un laboratorio farmacéutico nacional-Trujillo 2018 - Amaya Abanto, Andrews Victor Humberto (2019)
This report of pre-professional practices is entitled: "Physicochemical quality of the finished product Dorzolamide 2% + Timolol 0.5% ophthalmic solution of a national pharmaceutical laboratory, Trujillo 2018", and aims to evaluate the physicochemical quality of this medicine by means of the corresponding tests according to USP 41. The sample consisted of 60 ophthalmic solutions obtained randomly during the packaging. The results obtained from the finished product were the following: Description: Transparent, colorless, slightly viscous solution. Free of visible particles; Identification: The RF values of the main spots of the sample solution corresponded to those of the main spots obtained from the standard solutions of Timolol Maleate and Dorzolamide Hydrochloride, respectively by thin layer chromatography. The retention time of the main peak of the sample solution corresponded to that of the standard solution, as obtained in the assessment of Dorzolamide and Timolol respectively by high performance liquid chromatography. The average volume was 5.2 mL and the pH was 5.78; Titration: 5.00 mg / mL of Timolol (100.0%) and 20.36 mg / mL of Dorzolamide (101.8%). The results of the particle counting test for light obstruction as well as the assay of organic impurities of Dorzolamide hydrochloride and Timolol maleate complied with the official USP 41 standard. It is concluded that Dorzolamide 2% + Timolol 0.5% ophthalmic solution meets the specifications stated in USP 41.